Further insights into exporter profiles: a classificatory model - María Jesús Ruiz Fuensanta (European Regional Science Association (ERSA), 2004)
One of the most relevant developments in the recent decades has been the progressive internationalisation of the world economy. To a great extent, physical borders have been removed by technological advancement, and this fact has made possible a rapprochement between countries and their respective cultures. For firms, this situation offers a range of possibilities owing to market increase. But, at the same time, domestic firms will have to face a rise in competition, and, probably, a market share decrease caused by the presence of foreign firms in their local market. Thus, to ensure survival, international expansion of firms' activities becomes a necessity more than just an option. Despite this evidence, not all firms feel inclined to tackle their internationalisation process. Even between firms already sending their products abroad, it is possible to distinguish those ones that are fully engaged in export activity from those that just consider it an occasional task. That is to say, all exporters have neither the same international orientation, nor show the same export intensity. Consequently, grouping exporters in a single category could be misleading and could also hinder obtaining solid results in this research area. Furthermore, such a classification can counteract the efficiency of governmental export assistance programmes.The aim of this paper is to carry out a closer examination of the differences between active and passive exporters. With this purpose in mind, we first submit the considered variables to a non-parametric test in order to select those ones that better differentiate between both groups of exporters. Once the most relevant disparities are discovered, the significant variables are used to elaborate a classificatory model via a logistic function. The empirical analysis is based upon data collected from small and medium sized manufacturing firms located in Castilla-La Mancha, an inland region of Spain. The results indicate that a firm's international experience and export intensity, and managers' perceptions of foreign trade barriers are the most effective variables for distinguishing active from passive exporters. The obtained model accurately classifies 93% of cases. Finally, these findings allow us to formulate some policy recommendations that, probably, will increase the efficiency of export promotion expenditures.
Keywords: 330